[Translated article] SARS-CoV-2 Infection in Patients With or at Risk for Venereal Infections: Incidence and Associated Factors in a Sexual Health Clinic - A. Martin-Gorgojo; M. Menéndez-Orenga; A. Comunión-Artieda; R. Martín-Pozas; P. Montero-Rivas; F.- (Elsevier, 2023)
Background and objective: SARS-CoV-2 is more easily spread by close contact, which is inherent to sexual intercourse. People with, or at risk for, sexually transmitted infections (STIs) may therefore have higher rates of COVID-19. The aim of this study was to estimate SARS-CoV-2 antibody seroprevalence in people seen at a dedicated STI clinic, compare our findings to the estimated seroprevalence in the local general population, and study factors associated with SARS-CoV-2 infection in this setting. Material and methods: Cross-sectional observational study including consecutive patients older than 18 years of age who had not yet been vaccinated against COVID-19 and who underwent examination or screening at a dedicated municipal STI clinic in March and April 2021. We ordered rapid SARS-CoV-2 serology and collected information on demographic, social, and sexual variables, STI diagnoses, and history of symptoms compatible with SARS-CoV-2 infection. Results: We studied 512 patients (37% women). Fourteen (24.2%) had a positive SARS-CoV-2 test. Variables associated with positivity were use of FFP2 masks (odds ratio 0.50) and a higher-than-average number of sexual partners (odds ratio 1.80). Use of FFP2 masks was not randomly distributed in this sample. Conclusions: Sexually active members of the population in this study had a higher incidence of SARS-CoV-2 infection than the general population. The main route of infection in this group appears to be respiratory, linked to close contact during sexual encounters; sexual transmission of the virus is probably limited. Resumen: Antecedentes y objetivo: El SARS-CoV-2 se transmite con más facilidad por cercanía física, inherente a las relaciones sexuales, lo que ha hecho plantearse que pueda haber una mayor incidencia de COVID-19 en personas con infecciones venéreas o de transmisión sexual (ITS) o en riesgo de adquirirlas. Por este motivo, buscamos estimar la seroprevalencia de anticuerpos frente a SARS-CoV-2 en personas que acuden a una consulta monográfica de ITS, comparar dicha seroprevalencia con la estimada en nuestra región y estudiar los factores asociados. Material y método: Estudio observacional transversal que incluye a pacientes mayores de 18 años aún no vacunados atendidos en una consulta monográfica municipal de ITS para estudio o cribado, incluidos de forma consecutiva de marzo a abril de 2021. Se realizó test serológico rápido para SARS-CoV-2, y se recogieron variables demográficas, sociales y sexuales, diagnósticos de ITS y antecedentes de síntomas compatibles con infección por SARS-CoV-2. Resultados: Se incluyó a 512 pacientes, el 37% mujeres. Ciento veinticuatro pacientes (24,2%) tuvieron alguna prueba positiva a SARS-CoV-2. Se relacionaron con un resultado positivo: el uso de mascarillas tipo FFP2 (OR: 0,50) y el número de parejas sexuales superior a la mediana (OR: 1,80). El uso de mascarillas FFP2 no se distribuyó de manera aleatoria en la muestra. Conclusiones: La población sexualmente activa ha tenido pruebas positivas a SARS-CoV-2 con más frecuencia que la población general. La principal vía de contagio en este grupo parece ser la vía respiratoria, por lo que la transmisión sexual es probablemente limitada y está relacionada con la proximidad que implican las relaciones sexuales.